(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This study explores the development of an electrolytic method for extracting tungsten powder from WC-Co based hard alloy wastes, specifically VK6, VK8, and VK15 grades. Considering the high cost and scarcity of tungsten and cobalt, recycling worn-out hard alloys has become an industrial necessity. The research evaluates the effectiveness of electrolytic processing using sulfuric and nitric acid solutions. Experiments were conducted under varying concentrations, temperatures, and current types to optimize tungsten recovery and minimize environmental impact. Analytical methods such as SEM and EDXRF were used to assess the chemical composition of the resultant powders, with findings showing high tungsten content and effective cobalt separation. The results suggest that sulfuric acid solutions are more effective in producing high-purity tungsten powder with reduced carbon and oxide impurities.